2012
DOI: 10.1186/1476-0711-11-26
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic-resistance Staphylococcus aureus isolated from cow’s milk in the Hawassa area, South Ethiopia

Abstract: BackgroundQuarter milk samples from cows were examined to determine the prevalence of Staphylococcus aureus (SA) and different antibiotic resistant pattern were determined in a cross-sectional study design.ObjectiveThe objective of this study was to isolate Staphylococcus aureus from samples of cow’s milk obtained from Hawassa area and to determine their antibiotic susceptibility patterns.MethodA total of 160 milk (CCP1-CCP5) samples were collected and screened for the presence of S. aureus. Gram staining, oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
71
21
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 27 publications
31
71
21
2
Order By: Relevance
“…This finding is inconsistent with the earlier findings of in Holleta agricultural research centre (43.3%) by [25] in Hawassa area (48.75%) by [13] and in Holeta town (47.1%) by [26]. Similarly, this result was in line with the previous findings of [21,30,31] who have reported as 40.3%, 39.1% and 39.2% and S. aureus isolates at Assela, Addis Ababa and Southern Ethiopia, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is inconsistent with the earlier findings of in Holleta agricultural research centre (43.3%) by [25] in Hawassa area (48.75%) by [13] and in Holeta town (47.1%) by [26]. Similarly, this result was in line with the previous findings of [21,30,31] who have reported as 40.3%, 39.1% and 39.2% and S. aureus isolates at Assela, Addis Ababa and Southern Ethiopia, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies have been carried out in some areas of Ethiopia to assess the status of Staphylococcal mastitis [10][11][12][13]. However, there was any study done to assess the status of S. aureus and/ or MRSA in and around Asossa districts, Benishangul Gumuz regional state, Western Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The total prevalence in this study is in line with 29.1% [11] and 27% [12] in Debrezeit, Ethiopia. In the other side, the study done by Daka et al [13], in Southern Ethiopia found very high prevalence than this study which is reported as 40.6%. The difference may come due to the study site Southern Ethiopia includes small holders with a probability of high contamination due to poor hygienic standards.…”
Section: Discussioncontrasting
confidence: 65%
“…Although oxacillin resistance is rare in S. aureus strains, some of them could be resistant to methicillin or oxacillin and lack the gene coding for antibiotic resistance (12). The inconsistency in the frequency and extent of antimicrobial resistance reported by studies in Iran and rest of the world (15,(17)(18)(19)(20)(21) could be due to different of the techniques used, geographic area, and type of samples collected and common antibiotics prescribed during a particular period of time. High level of contamination in raw milk could have several reasons including cross-contamination caused by preparation by hand and failure to comply with code of hygienic practices for the milking process.…”
Section: Discussionmentioning
confidence: 99%
“…Daka et al found 78 S. aureus isolates in 160 raw milk samples collected in Ethiopia. All the isolates were resistant to penicillin G and the highest level of resistance was observed against amoxicillin (70.9%), penicillin (67.9%), oxacillin (60.3%) and vancomycin (38.5%) (18). Joshi et al studied 400 milk samples and found 119 (29.7%) S. aureus isolates with 97.47%, 94.95%, 91.59% and 89.9% susceptibility to ciprofloxacin, gentamicin, ceftriaxone and tetracycline, respectively (19).…”
Section: Discussionmentioning
confidence: 99%